SOIL EROSION MODELING AND CONSERVATION PRIORITY MAPPING IN THE TIRTOMOYO SUB-WATERSHED - MS Khabibur Rahman; Anggun Deristani; Pranichayudha Rohsulina; Célestin Havyarimana (GeoEco, 2026)
The Tirtomoyo sub-watershed is characterized by highland topography and is currently under considerable pressure from anthropogenic activities. Such conditions have contributed to significant soil erosion, which poses a major threat to land productivity and environmental sustainability in the area. The main objective of this research is to analyze the potential soil loss within the sub-watershed. The Universal Soil Loss Equation (USLE) method was applied, as it provides a systematic approach to understanding the relationship between soil loss and the contributing factors of erosion. These factors include soil erodibility (K), slope length and steepness (LS), land use (C), land management practices (P), and rainfall erosivity (R). The unit of analysis was based on land mapping units, allowing for spatially detailed assessment of erosion vulnerability. The results of the study indicate that the Tirtomoyo sub-watershed exhibits varying degrees of erosion susceptibility, with moderate erosion being the most dominant class. The physical condition of the area, consisting of rolling to steep terrain, combined with insufficient vegetation cover and limited conservation practices, has exacerbated soil loss. Field observations also identified the presence of gully erosion, where concentrated surface runoff has carved deep and wide channels, highlighting the severity of land degradation in certain locations. These findings emphasize the urgency of implementing appropriate land management strategies to reduce the erosion rate. Measures such as vegetation restoration, terracing, and improved soil conservation practices are essential to maintain land productivity and minimize environmental impacts.